Dreamboat on Word - Troy, Anne (Holy Macro! Books, 2003)
Written for intermediate- to expert-level Microsoft Word users, this book demonstrates frequently missed tools and the proper way to use new and existing tools. Word's settings, toolbars, and menus are reviewed, as are topics such as the importance of installing safe fonts, setting tabs correctly, and using styles for maximum effect. Also offered is advice on topics pertaining to work groups, such as sharing templates, styles, and toolbars and creating paper and paperless forms. New concepts such as using tables to set up forms, recording macros to cut down on repetition, automatically updating cross-references, and minimizing file sizes are covered. Instructions on keeping a hard drive clean, which can minimize general PC problems, are also provided.